EFISIENSI RELATIF AGROINDUSTRI PALA BANDA DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - N.R. TIMISELA; M. TURUKAY; W.B. PARERA; MARVIN LAWALATA (Universitas Sebelas Maret, 2012)
Agro-industry is an industrial activity that process agricultural raw materials into another form of the more interesting and adds value, be efficient and have a high selling value. This study aims to assess the relative efficiency of agroindustry enterprises Banda nutmeg using DEA (Data Envelopment Analysis) concept which is a measure of efficiency that are free value (value-free) because it is based on data available regardless of the judgment (judgment) of the decision makers responsible for using a number of inputs to obtain an output targeted.